2018
DOI: 10.1515/htmp-2016-0188
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Non-metallic Inclusions of Si-killed Stainless Steel during GOR Refining Process

Abstract: The formation mechanism of inclusions in Si-killed 304 stainless steel was studied by industrial experiments during GOR refining process and thermodynamic calculations. A lager number of CaO-SiO2-MgO-Al2O3-MnO-CrOx liquid spherical inclusions with different size (from 1 μm to 22 μm) had been found after deoxidization of FeSi alloy in 10 minutes. The calculation result of FactSage 6.3 software assisted in confirming that the inclusions in size of less than 5 μm that had less than 30 % CaO mainly came from the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…[1,2] Its operations have indicated the advantages in terms of high decarbonization rate, high chromium yield, low argon consumption, and high furnace age, etc. [3][4][5][6] In recent years, physical and mathematical simulations have been widely used to study the fluid flow and transport phenomena in metallurgical reaction vessels, such as converters and ladles. The fluid pattern of the gas-liquid flow and the bubble distribution were investigated using the Eulerian volume of fluid (VOF) model and the Lagrangian discrete phase model (DPM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Its operations have indicated the advantages in terms of high decarbonization rate, high chromium yield, low argon consumption, and high furnace age, etc. [3][4][5][6] In recent years, physical and mathematical simulations have been widely used to study the fluid flow and transport phenomena in metallurgical reaction vessels, such as converters and ladles. The fluid pattern of the gas-liquid flow and the bubble distribution were investigated using the Eulerian volume of fluid (VOF) model and the Lagrangian discrete phase model (DPM).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] Its operations have indicated the advantages in terms of high decarbonization rate, high chromium yield, low argon consumption, and high furnace age, etc. [ 3–6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Evolution of inclusions in 304 stainless steels at production steps have been widely studied . However, less attention has been paid to the variation of inclusions during the heat treatment of stainless steels.…”
Section: Introductionmentioning
confidence: 99%
“…The control of the composition, quantity, and size of the inclusions at the beginning of their formation is likely to become a new and effective method to reduce the harmful influence of the inclusions. Therefore, it is very important to investigate the source and formation mechanism of the inclusions [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The formation of non-metallic inclusions of Si-killed stainless steel during the GOR (gas oxygen refining) process has been reported by Li et al [7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to investigate the source and formation mechanism of the inclusions [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The formation of non-metallic inclusions of Si-killed stainless steel during the GOR (gas oxygen refining) process has been reported by Li et al [7]. The authors found that the inclusions that were larger than 5 µm and contained more than 30% CaO were attributed to the modification of slag droplets through the oxidation of Si and Al and the collision with deoxidation-type inclusions; in addition, the degree of change was larger for the smaller inclusions.…”
Section: Introductionmentioning
confidence: 99%